2017
DOI: 10.22161/ijeab/2.6.21
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Profitability and Constraints of Table Egg Production Enterprises in Benue State, Nigeria

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…For Malawi, pond size was found to have a positive but insignificant influence on technical efficiency. The result supports earlier findings by Tung, Penda et al, Huy, Alam and Murshed-e-Jahan, and Ogundari and Ojo [51,[55][56][57][58].…”
Section: Discussionsupporting
confidence: 92%
“…For Malawi, pond size was found to have a positive but insignificant influence on technical efficiency. The result supports earlier findings by Tung, Penda et al, Huy, Alam and Murshed-e-Jahan, and Ogundari and Ojo [51,[55][56][57][58].…”
Section: Discussionsupporting
confidence: 92%
“…Preliminary survey showed that despite the abundant production of some livestock feed materials like soya beans and maize, Benue State has not been able to meet up with the increase demand in poultry meat and egg. Benue State still depends on neighbouring States of Enugu and Plateau for her egg needs [14,15]. This huge market has been left for entrepreneurs from other States.…”
Section: Introductionmentioning
confidence: 99%